Resource co‐limitation of community biomass but not structure of an alpine grassland - Juntao Zhu; Ning Zong; Peili Shi; Yunlong He; Xian Yang; Yangjian Zhang; Lin Jiang (Ecology, 2023)
Anthropogenic environmental changes are influencing the structure and function of many ecological communities, but their underlying mechanisms are often poorly understood. We conducted a 7‐year field experiment to explore the ecological consequences of nitrogen (N) and phosphorous (P) enrichment in a high‐altitude Tibetan alpine grassland. We found that the enrichment of both N and P, but not either alone, increased plant above‐ and belowground biomass. In contrast, N, but not P, enrichment reduced species richness and altered plant phylogenetic diversity and structure. Whereas plant species loss and changes in phylogenetic structure were mainly driven by higher soil manganese levels under N addition, they were mainly driven by increased plant belowground biomass under the addition of both N and P. Our study highlights the resource co‐limitation of community biomass but not the structure of the study grassland, while also identifying soil metal toxicity and belowground competition as important mechanisms driving community changes following nutrient amendment.